Pertussis Vaccine CNS Sequelae Reassessment - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The role of whole-cell pertussis vaccine as a cause of permanent neurologic damage has been reassessed by the American Academy of Pediatrics, Committee on Infectious Diseases, in light of new 10-year follow-up findings of the National Childhood Encephalopathy Study (NCES) in Great Britain.